Use of English at the Workplace : How Far is this True in Malaysia? - Noor Hanim Rahmat; Normah Ismail; Azizah Daut (Indonesian JELT, 2015)
According to Ong etal. (2011), the importance of English in theMalaysian work environment is the main concern of manyemployers. Some employers reported that having employees withbetter English would improve productivity. How far is Englishbeing used at the workplace in Malaysia? This quantitative studytargets at possible direction of a language programme such asEnglish for Specific Purpose especially for Occupational andVocational purposes. It looks into how much English is used atselected industries in Malaysia. Specifically, it reports on howcommunication in English is used at different departments inselected industries as well as how the use differs across agegroups, genders and industries. Results of this study will haveinteresting implication for future English for business purposescourses.(125 words)Keywords: work environment, industries, communication